Sebastian and the balloon - Stead, Philip Christian (Roaring Brook Press, 2014)
"When Sebastian launches himself on a journey in a hot air balloon made entirely of Grandma's afghans and patchwork quilts, his boring day turns into the adventure of a lifetime"--